Evaluating object recognition ability in developmental prosopagnosia using the Cambridge Car Memory Test. Issue 1 (17th February 2019) - Gray, Katie L. H.; Biotti, Federica; Cook, Richard
ABSTRACT: Individuals with developmental prosopagnosia (DP) sometimes experience object identification difficulties in addition to problems recognizing faces. To better understand the distribution of non-face object recognition ability in this population, we administered the Cambridge Car Memory Test (CCMT) – a leading, standardized measure of object recognition ability – to a large sample of DPs (N = 46). When considered as a single group, the DPs scored lower than matched controls. This finding provides further evidence that developmental object agnosia (DOA) may be more common in DP than in the general population. Relative to the DPs' face recognition deficits, however, car matching deficits were small and inconsistent. In fact, we observed a striking range of CCMT performance in our DP sample. While some DPs performed extremely poorly, many more achieved scores within one standard deviation of the typical mean, and several DP participants achieved excellent CCMT scores comparable with the best controls.